2021
DOI: 10.1002/adma.202100359
|View full text |Cite
|
Sign up to set email alerts
|

Quicker and More Zn2+ Storage Predominantly from the Interface

Abstract: Aqueous zinc‐ion batteries are highly desirable for large‐scale energy storage because of their low cost and high‐level safety. However, achieving high energy and high power densities simultaneously is challenging. Herein, a VOx sub‐nanometer cluster/reduced graphene oxide (rGO) cathode material composed of interfacial VOC bonds is artificially constructed. Therein, a new mechanism is revealed, where Zn2+ ions are predominantly stored at the interface between VOx and rGO, which causes anomalous valence chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(74 citation statements)
references
References 40 publications
3
71
0
Order By: Relevance
“…From 0.5 to 32 A g –1 , the capacity retention rate of the VO 2 -SDBS@rGO electrode is 77.6%, showing its excellent rate performance. The quicker and more Zn 2+ storage may be triggered by interface-dominated electrons and Zn 2+ ion storage between VO 2 and rGO . We also juxtapose the energy density and power density with some recently reported studies in Figure e.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…From 0.5 to 32 A g –1 , the capacity retention rate of the VO 2 -SDBS@rGO electrode is 77.6%, showing its excellent rate performance. The quicker and more Zn 2+ storage may be triggered by interface-dominated electrons and Zn 2+ ion storage between VO 2 and rGO . We also juxtapose the energy density and power density with some recently reported studies in Figure e.…”
Section: Resultsmentioning
confidence: 58%
“…For example, Lan et al studied the reduced graphene oxide (rGO)-modified FeVO 4 · n H 2 O@rGO cathode material, which has a fast electron transfer rate and excellent zinc ion storage performance. Moreover, the latest research has revealed an interface storage mechanism between VO x and rGO, which enables the interface to store more Zn 2+ . Therefore, improving the hydrophilicity internally and coating with rGO externally are predominant ideas to enhance the performance of ZIB electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, various cathode materials, such as MnS, 8 VS 2 , 9 Na 3 V 2 (PO 4 ) 3 , 10 LiV 3 O 8 , 11 Zn 0.25 V 2 O 5. nH 2 O, 12 V 2 O 5 , 13,14 VO 2 , 15 VO x @rGO, 16,17 Mg x MnO 2 , 18 MnO 2 , 19,20 and Mn 3 O 4 , 21 have been explored for AZIBs. Among them, manganese oxides are highly attractive cathode candidates for AZIBs because they can be easily prepared using affordable Mn resources and oxygen from the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Global prosperity demands energy security that entails reliable energy storage systems with inerrable safety. [1][2][3][4] Recently, aqueous batteries that employ metal anodes have attracted much attention. [5][6][7][8] The emerging aqueous batteries differ from the well-established alkaline metal batteries, many of which are primary batteries; [1] new aqueous batteries often employ neutral or mildly acidic electrolytes that exhibit a wider electrochemical stability window.…”
Section: Introductionmentioning
confidence: 99%